Direct and Indirect Effects of Sex Steroids on Gonadotrope Cell Plasticity in the Teleost Fish Pituitary - Fontaine, Romain; Royan, Muhammad Rahmad; von Krogh, Kristine; Weltzien, Finn-Arne; Baker, Dianne M. (Frontiers in Endocrinology, 2020)
The pituitary gland controls many important physiological processes in vertebrates, including growth, homeostasis and reproduction. As in mammals, the teleost pituitary exhibits a high degree of plasticity. This plasticity permits changes in hormone production and secretion necessary to meet the fluctuating demands over the life of an animal. Pituitary plasticity is achieved at both cellular and population levels. At the cellular level, hormone synthesis and release can be regulated via changes in cell composition to modulate both sensitivity and response to different signals. At the cell population level, the number of cells producing a given hormone can change due to proliferation, differentiation of progenitor cells, or transdifferentiation of specific cell types. Gonadotropes, which play an important role in the control of reproduction, have been intensively investigated during the last decades and found to display plasticity. To ensure appropriate endocrine function, gonadotropes rely on external and internal signals integrated at the brain level or by the gonadotropes themselves. One important group of internal signals is the sex steroids, produced mainly by the gonadal steroidogenic cells. Sex steroids have been shown to exert complex effects on the teleost pituitary, with differential effects depending on the species investigated, physiological status or sex of the animal, and dose or method of administration. This review summarizes current knowledge of the effects of sex steroids (androgens and estrogens) on gonadotrope cell plasticity in teleost anterior pituitary, discriminating direct from indirect effects.